Multimedia Interaktif Menggunakan Articulate Storyline Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Pada Materi Larutan Penyangga - Wafiqah Alvia Ramadhani; Syamsurizal Syamsurizal; Afrida Afrida (Hydrogen: Jurnal Kependidikan Kimia, 2022)
With the passage of time, it frequently raises issues in the teaching and learning process in the classroom, which is thought to be less effective because teachers are less able to adapt to the times they face.These problems can affect the quality of education in Indonesia, so solutions are needed to overcome them. The purpose of this study is to determine whether the interactive multimedia development procedure with a scientific approach can specifically help improve students' critical thinking skills on buffer solution material, as well as whether the developed media is theoretically or practically feasible. This research method adheres to the Lee and Owens development model, which is divided into five stages: analysis, design, development, implementation, and evaluation.The results showed interactive multimedia with a scientifically validated approach as digital teaching materials that met the requirements to support a special learning process for students with visual learning styles. This interactive multimedia got a very good response with a percentage of 92.85%. It is then reinforced by positive posttest results and has an impact on increasing students' critical thinking skills with a gain index of  0,7(medium category).